PP-039 Impact of masking on methylphenidate dissolution for over encapsulated capsules of ritalin la 10 mg. (25th February 2017) - Cornille, M; Lannoy, D; Bourdon, F; D'Horne, C; Berneron, C; Devos, D; Simon, N; Odou, P
Abstract : Background: As part of the development of a double blind clinical trial using Ritalin LA (extended release) 10 mg containing methylphenidate hydrochloride (MH), over-encapsulated capsules have to be compounded and MH release studied. This release is bimodal (SODAS technology), with the first 50% of the dose released immediate at strong acidic pH, and the second 50% release at a pH >6. Capsules and backfilled excipient used for masking Ritalin LA capsules have a potential impact on MH release, compared with bare capsules. Purpose: To study the potential impact of masking in over-encapsulated capsules with microcrystalline cellulose (MC), on in vitro biopharmaceutical parameters. Material and methods: A dissolution study was carried out by comparing MH release from bare capsules (n=6) with over-encapsulated capsules (n=6) using MC as the backfilled excipient. The two release phases of MH were studied in a unique dissolution medium. A Britton–Robinson buffer, pH 2, was used for 2 hours at 37°C. Then, the same buffer was adjusted to pH 6.8 for a 5 hour dissolution time. The basket dissolution apparatus (European Pharmacopoeia (EurPh) 2.9.3) was used at 50 rotations/min. 15 samples of 2 mL were filtrated using cellulose acetate membrane filters. MH dosing was quantified by a stability indicating (HPLC-UV-diode array detector) method. The two dissolution profiles were compared with fit factors (difference factor f1 <15%, similarity factor f2 >50% for similarity) and the Rescigno index (zeta1 and zeta2 with values close to 0 tending toward similarity). A disintegration test (EurPh 2.9.1) was led on 6 capsules. Statistical analysis was conducted using non-parametric tests (α < 5%). Results: On the whole dissolution, fit factors and Rescigno index were: f1 =2.2% f2 =96.0% zeta1 =0.012 zeta2 =0.025 A lag time of a few minutes at the beginning of dissolution was observed for over-encapsulated capsules. This can be explained in part by the delay in capsule disintegration (103 s and 170s (p<0.001) for, respectively, bare and encapsulated capsules). MH progressive degradation was highlighted in buffers, which explains why the maximum amount was < 100% (median on first phase of 47.85% and 47.1% (NS) and on the second phase 42.5% and 43.3% (NS)). Conclusion: A similarity between over-encapsulated and bare capsules was demonstrated using MC. No conflict of interest